Global climate change : the economic costs of mitigation and adaptation - White, J. C. (Jonathan Curtis), 1952-; White, J. C. (Jonathan Curtis), 1952-; Wagner, William; Beal, Carole N.; Center for Enviromental Information (U.S); Global Climate Change: The Economic Costs of Mitigation and Adaptation (1990 : Washington D C) (New York : Elsevier, 1991)
40